THE ROLE OF GOOD CORPORATE GOVERNANCE IN EFFORT TO IMPROVE ENVIRONMENTAL QUALITY THROUGH EMPHASIS ON SUSTAINABILITY REPORT - Lailah Fujianti Genda; Detatiara Riesya Nugroho; Nelyumna (FEB-UP Press, 2021)
This study is a study of the influence of Good Corporate Governance on the sustainability reportof manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample in this study were 40 using purposive sampling method. Guidelines in calculating the sustainability reportindex score use the Global Reporting Initiative (GRI) G4 with 91 indicators. The method used in analyzing data uses Eviews 9 with multiple linear regression. The results showed that company board of directors had no effect on the sustainability report. Meanwhile, audit committee, and the Board of Commissioners have a negative effect on the sustainability report. It is hoped that this research can be useful and can be used as a guide by management in disclosing sustainability reports. Furthermore, investors are expected not only to see the company's financial performance but also to disclose the company's sustainability report. That way investment can be decided appropriately.